2016
DOI: 10.3748/wjg.v22.i38.8558
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of hepatitis C infected patients treated through an integrated care model

Abstract: AIMTo determine if our health system’s integrated model reflects sustained virologic response (SVR) outcomes similar to those in clinical trial data, maximizes adherence, and averts drug interactions.METHODSSubjects with chronic hepatitis C had their medical records reviewed from November 1st, 2014 through March 1st, 2016. Patients eligible for treatment were entered into an integrated care model therapy algorithm. The primary outcome was SVR12 based on intention to treat (ITT) analysis. Inclusion criteria con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The adherence rate was not influenced by the dosage form (either the combination tablets or the non-combination tablets). Some previous reports have indicated that the SVR12 rate is 88.2–95.3% in real-world settings [ 9 , 12 , 16 18 ], and 84.4–98.1% in phase 2–3 trials [ 15 , 19 21 ]. In this study, the SVR12 rate was 99.6% (Table 2 ), which is relatively higher than in the previous studies [ 9 , 12 , 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adherence rate was not influenced by the dosage form (either the combination tablets or the non-combination tablets). Some previous reports have indicated that the SVR12 rate is 88.2–95.3% in real-world settings [ 9 , 12 , 16 18 ], and 84.4–98.1% in phase 2–3 trials [ 15 , 19 21 ]. In this study, the SVR12 rate was 99.6% (Table 2 ), which is relatively higher than in the previous studies [ 9 , 12 , 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous reports have indicated that the SVR12 rate is 88.2–95.3% in real-world settings [ 9 , 12 , 16 18 ], and 84.4–98.1% in phase 2–3 trials [ 15 , 19 21 ]. In this study, the SVR12 rate was 99.6% (Table 2 ), which is relatively higher than in the previous studies [ 9 , 12 , 16 18 ]. These results indicate that the pharmaceutical support provided by the ambulatory care pharmacy practice, including explanation of the importance of adherence and the management of adverse drug events, helped the achievement of favorable SVR rates, probably due to the enhancement of adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment initiation increased 2- to 3-fold and on-site patients receiving more services had higher odds of initiating treatment [ 16 ]. Another recent study used a multidisciplinary team focused on educating patients before antiviral treatment and facilitating medication adherence in an HMO setting [ 17 ]. The study lacked a comparison group but obtained SVR rates in an outpatient HMO setting similar to those found in highly controlled clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists may also contribute directly to therapy monitoring either in clinic or via telemedicine. Studies have demonstrated improved adherence in addition to preventing drug-drug interactions and medication errors with pharmacy involvement [ 50 53 ]. More than 50% of HCV patients treated in a multidisciplinary model consisting of an infectious diseases physician, HCV nurse, and specialty pharmacist were identified to have drug-drug interactions requiring interventions by a pharmacist [ 50 ].…”
Section: Treatment Monitoringmentioning
confidence: 99%